Frequency of Urinary Tract Infection in Severe Acute Malnutrition Children Presenting at Lady Ready Hospital Peshawar - Rahman, Momina; Hayat, Mohsin; Muhammad, Mian; Syed, Annam; Shafiq, Fatima; Rasool, Palwasha (Indus Journal of Bioscience Research, 2025)
Background: Severe acute malnutrition (SAM) significantly impairs immune defenses, predisposing children to infections such as urinary tract infections (UTIs). UTIs in this group may often go undetected due to atypical presentations and resource-limited settings. This study aimed to determine the frequency of UTIs among children with SAM presenting to a tertiary care hospital in Peshawar, Pakistan. Methods: The study is a descriptive cross-sectional that was undertaken at the Department of Pediatrics, Lady Reading Hospital, Peshawar, and lasted six months (Nov 2023 to APRIL 2024). 175 children aged 1 to 5 years old having SAM according to WHO criteria were recruited by consecutive sampling. Sterile collection of urine and assessment of UTI according to traditional microbiological parameters was undertaken. Demographic, socioeconomic background, residence and maternal educational data as well as analyzing it by using SPSS. Results: UTI was diagnosed in 30 (17.1%) of 175 children with severe acute malnutrition. UTI prevalence was higher among younger children (1–2 years), rural residents (76.7%), children from low socioeconomic status (86.7%), and those with illiterate mothers (76.7%). Statistically significant associations were found between UTI and socioeconomic status (p = 0.048), residence (p = 0.049), and maternal education (p = 0.032). No significant correlation was observed between UTI and gender or age group. Conclusion: Frequency of UTI is higher among children with SAM, particularly in socioeconomically disadvantaged and rural populations. Routine screening for UTI in malnourished children may help prevent serious complications and improve overall clinical outcomes. Health education and improved access to sanitation and healthcare services are crucial in addressing this burden.